1975
DOI: 10.1210/endo-97-2-399
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Precocious Sexual Maturation in the Immature Rat Treated with Dehydroepiandrosterone1

Abstract: The normal weight increase of the epididymis during sexual maturation and its maintenance through adulthood were found to be dependent on the provision of androgens. Binding of [3H]dihydrotestosterone (DHT) to the epididymal 8S cytoplasmic receptor gradually decreased after castration to become undetectable after 25 days. Binding to the androgen binding protein (ABP) was absent 4 days after castration and was not reinduced by 3 weeks of testosterone (T) administration. Unilateral castration for periods of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…There is no evidence in the literature that the AR is involved in the advancement of VO. Contrary to the actions of estrogen and aromatizable androgens, nonaromatizable androgens either have no effect on the onset of puberty or delay it [9,10]. Taken together, the results of the present experiments suggest that stanozolol may be acting at the vaginal ER to advance VO.…”
Section: Mechanism and Site Of Actioncontrasting
confidence: 60%
See 1 more Smart Citation
“…There is no evidence in the literature that the AR is involved in the advancement of VO. Contrary to the actions of estrogen and aromatizable androgens, nonaromatizable androgens either have no effect on the onset of puberty or delay it [9,10]. Taken together, the results of the present experiments suggest that stanozolol may be acting at the vaginal ER to advance VO.…”
Section: Mechanism and Site Of Actioncontrasting
confidence: 60%
“…In contrast to the advancement of puberty by estrogen and aromatizable androgens, treatments with nonaromatizable androgens delay the onset of puberty [9,10]. Thirty-day treatment with one AAS, stanozolol, has differential effects on pubertal endpoints in female rats.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies using co-administration of DHEA and the antiestrogen Acolbifene or the antiandrogen FLU, respectively, have demonstrated that the action of DHEA in the rat mammary gland [42], skin sebaceous glands [43] and bone mineral density [44] is almost exclusively androgenic. Nevertheless, the presence of an estrogenic action of DHEA in the rat vagina has been previously demonstrated, either by the formation of a stratified epithelium in the vagina of rats treated with FLU and DHEA (unpublished data), or through induction of vaginal opening and precocious ovulation in immature rats treated with this compound, while DHT, an androgen not aromatizable to estrogens, did not produce such effects [45]. The capacity of rat vaginal tissue to aromatize androgens, especially, Testo, is likely to account for the major part of the estrogenic effect of DHEA in this organ [46].…”
Section: Discussionmentioning
confidence: 89%
“…Subsequent studies confirmed that the DHEA-PCO rat model exhibits many of the salient features of human PCO. The administration of DHEA induces cystic changes in the ovaries of immature female rats, in conjunction with precocious ovulation, acyclicity, and anovulation [9][10][11]. Similarly, ovarian cysts are noted when DHEA is given to adult cycling rats [12].…”
Section: Introductionmentioning
confidence: 99%